The Virtues of the Righteous Woman in the Dimension of Islamic Religious Education and Their Correlation with Household Harmony - Iesy Naely Fithrotun Nisa; Moh. Ali; Sugianto; Taqiyuddin; Ali Shodiqin (Yayasan Ilomata, 2026)
This study examines the phenomenon of early marriage, commonly associated with social pressures transmitted through family expectations, community norms, and media discourse, which may also affect urban women, including civil servants in the education sector. Such pressures are often linked to vulnerabilities in domestic relationships, including potential verbal and non-verbal violence. Using a qualitative-descriptive literature review, this research systematically analyzes relevant academic sources to explore the role of Islamic Religious Education (PAI) values in shaping the personality of ṣāliḥah women as a form of psychosocial competence. The analysis focuses on three key themes: (1) the transmission of social norms from rural to urban contexts, (2) the conceptualization of ṣāliḥah women as encompassing emotional regulation, assertive communication, rights awareness, and coping strategies, and (3) the relationship between the internalization of PAI values and family relationship quality. The findings suggest that the internalization of religious values extends beyond normative dimensions, functioning as a psychosocial resource with the potential to act as a protective factor against social pressures and unhealthy domestic dynamics. However, this relationship remains conceptual and context-dependent. This study contributes by proposing a conceptual model positioning the ṣāliḥah construct as a psychosocial competence linking PAI value internalization to household harmony through self-regulation and adaptive social interaction. A key limitation is the absence of empirical validation due to its reliance on literature-based analysis.